Enhancement of fatigue resistance by overload-induced deformation twinning in a CoCrFeMnNi high-entropy alloy. (December 2020) - Lam, Tu-Ngoc; Lee, Soo Yeol; Tsou, Nien-Ti; Chou, Hung-Sheng; Lai, Bo-Hong; Chang, Yao-Jen; Feng, Rui; Kawasaki, Takuro; Harjo, Stefanus; Liaw, Peter K.; Yeh, An-Chou; Li, Ming-Jun; et al.
Abstract: We examined fatigue-crack-growth behaviors of CoCrFeMnNi high-entropy alloys (HEAs) under as-fatigued and tensile-overloaded conditions using neutron-diffraction measurements coupled with diffraction peak-profile analyses. We applied both high-resolution transmission electron microscopy (HRTEM) and neutron-diffraction strain mapping for the complementary microstructure examinations. Immediately after a single tensile overload, the crack-growth-retardation period was obtained by enhancing the fatigue resistance, as compared to the as-fatigued condition. The combined mechanisms of the overload-induced larger plastic deformation, the enlarged compressive residual stresses and plastic-zone size, the crack-tip blunting ahead of the crack tip, and deformation twinning governed the pronounced macroscopic crack-growth-retardation behavior following the tensile overload. A remarkable fracture surface of highly-periodic serrated features along the crack-propagation direction was found in the crack-growth region immediately after the tensile overload. Moreover, a transition of plastic deformation from planar dislocation slip-dominated to twinning-dominated microstructures in the extended plastic zone was clearly observed at room temperature in the overloaded condition, in accordance with the simulated results by a finite element method (FEM). The above tensile overload-induced simultaneously combined effects in the coarse-grained CoCrFeMnNi shed light on the improvement of fatigue resistance for HEAs applications. Graphical abstract: Image, graphical abstract